The Impact of Surroundings on the Characters in Thomas Hardyâ€™s Novels - Rahman, Suzana; Muntiningsih, Ratna (Academic Journal Perspective: Education, Language, and Literature, 2018)
TheÂ THEÂ IMPACTÂ OFÂ SURROUNDINGSÂ ONÂ THEÂ CHARACTERSÂ IN THOMAS HARDYâ€™S NOVELSâ€ is to apply the writersâ€™ knowledge on literature and to showÂ Â Â theirÂ interestÂ inÂ Â Â readingÂ novels.Â TheÂ writers transfered notÂ onlyÂ Â Â their limited knowledge in analysing novels as literary works but also building the awareness of the importance of reading habitÂ to their students of Unswagati because all of them take the subjectÂ ofÂ IntroductionÂ to EnglishÂ Literature.Â Â Â ReadingÂ andÂ analyzingÂ novelÂ isÂ really beneficialÂ forÂ students thatÂ Â Â bothÂ canÂ improveÂ theÂ studentsÂ readingÂ skillÂ butÂ alsoÂ their EnglishÂ ability,Â moreover,Â theyÂ willÂ haveÂ theÂ abilityÂ inÂ criticizingÂ theÂ novelÂ from differentÂ views.Â InÂ brief,Â itÂ willÂ alsoÂ improveÂ theirÂ criticalÂ thinking. Afterwards,Â by describing theÂ charactersÂ andÂ theirÂ attitudesÂ towardÂ eachÂ otherÂ andÂ howÂ the surroundings influence them, we also learn about their culture. The theory that is used in analysing those novels is from Harvey, Murphy, Klarer, and Lodge. The method that is applied in analysing the characters and the surroundings is descriptive qualiative in which the writers take the data by reading the three novels, explain in details about the charactersÂ andÂ theÂ surroundingsÂ involvedÂ inÂ theÂ story andÂ someÂ otherÂ elements supported the completeness of the story.